Panonska in makedonska teorija o jezikovni osnovi stare cerkvene slovanščine na prelomu iz 18. v 19. stoletje skozi prizmo genetolingvistike - Nikolovski, Gjoko (Studia Historica Slovenica, 2017)
The article deals with the question of the linguistic basis of the Old Church Slavonic, which was actualized at the turn of the 18th and 19th centuries, in the form of Pannonian and Macedonian theory, which offer a diametrically different answer. Advocates of Pannonian theory based on German and Latin borrowings, which are supposed to be present only in Slavic speech, spoken in areas close to Latin-German, for the language basis of Old Church Slavonic, determine the language of the Pannonian region, the language of the ancestors of Slovenes. The advocates of Macedonian theory on the basis of the voice similarities with the Old Church Slavonic determine the language of the surroundings of Thessaloniki for the language basis. Through the prism of genetolinguistics, we analyze the fate of these theories and their acceptability.
Keywords: primerjalno jezikoslovje; stara cerkvena slovanščina; zgodovinsko jezikoslovje